Social Determinants and Choices: Understanding Healthcare Utilization among Rural Women in Cross River State, Nigeria - Etobe, Eteng Ikpi; Iniama, Joshua; Etobe, Utibe E. I. (Current Progress in Arts and Social Studies Research Vol. 3, 2024)
This study analyses the factors that influence healthcare delivery among rural women in Cross River State, Nigeria, focusing on factors such as cultural norms and practices, and socioeconomic status. Rural women often face unique challenges in accessing and utilizing healthcare services, including limited access to healthcare resources, geographic isolation, and cultural and social barriers. To better understand the factors that influence healthcare delivery among rural women in Cross River State, Nigeria, this theoretical literature draws on social determinants that affect our choices of healthcare types and roots our understanding of these choices, using the social exchange theories. The significance of social and economic determinants of health, such as housing, education, and money, in influencing health outcomes is highlighted by social determinants of health. Conversely, social exchange theory highlights how social interactions and interpersonal relationships influence behavior and decision-making. Using these frameworks, we argue that healthcare utilization among rural women in Cross River State is influenced by a complex interplay of factors, including cultural beliefs about health and healthcare, socioeconomic status, gender roles, and access to healthcare resources. Our discussion, however, highlights the importance of social support networks and trust in healthcare providers in facilitating healthcare utilization among rural women. These factors can help mitigate the negative effects of geographic isolation and limited healthcare resources. Access to transportation is also critical in overcoming geographic barriers to healthcare utilization. Finally, we identify gender roles and cultural beliefs around healthcare as key barriers to access and utilization. To address these barriers and improve healthcare delivery for rural women, interventions may include community-based outreach programs, education on cultural competency for healthcare providers, and policies to address transportation barriers and other social determinants of health. By highlighting the significance of addressing social determinants of health and enhancing healthcare infrastructure to improve health outcomes for rural women, this paper adds to our understanding of the factors influencing healthcare delivery in rural areas. However, this report has consequences for researchers, social workers, politicians, and healthcare professionals who are trying to create interventions and policies that will effectively address healthcare disparities in rural regions.